Monuments of Ruination in Postwar Berlin and Warsaw: The Architectural Projects of Bohdan Lachert and Daniel Libeskind. (7th June 2017) - Meng, Michael
Abstract: This essay provides an interpretation of parallel attempts to represent ruination in the cities of Warsaw and Berlin after the Holocaust—the architectural projects of Bohdan Lachert and Daniel Libeskind. Lachert strove to represent the ruination of Jewish life in Warsaw through a modernist housing project, whereas Libeskind sought to represent Jewish ruination in a museum. While these two projects might seem different, they come together around a shared aspiration: to represent absence and ruination. Both projects endeavored to create a new kind of memorial that moved away from the conventional form. Rather than turning away from ruination and suffering as the conventional monument has done, Libeskind and Lachert sought to develop a new, non-salvific kind of monument that would reflect on death, suffering, and emptiness. This essay emphasizes the novelty of their attempts to create a different relationship to the absence that is the past, while it also explores some of the central challenges—both historical and theoretical—that both architects faced in implementing their artistic visions.